PEMBUATAN VIDEO LIVE SHOOT PENGENALAN PRODI TEKNIK MULTIMEDIA DAN JARINGAN POLIBATAM - Arta Uly Siahaan; Puspoadi Nugroho Pratama (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
Batam State Polytechnic is one of the public educational institutions inBatam, Riau Islands. It has several departments and study programs. One ofthem is the Informatics Engineering Department, which consists ofInformatics Engineering, Multimedia and Networking, Animation, and CyberSecurity Engineering. However, based on a 2017 survey by IndonesianCareer Center Network (ICCN), 85% of students choose the wrong major. Toovercome this problem, "Video Introduction to Polibatam Multimedia andNetwork Study Program using Live Shoot Method" was made. This video isanalyzed through 3 stages, Content Reviewers, Multimedia Reviewers andTesting to the Target Audience. Content Reviewers to assess aspects of videocontent, multimedia reviewers assess visual and audio aspects, while testingto the target audience assess visual, audio, content, language and writingaspects. The results obtained through testing to the target audience, the visualaspect were 85% this video is attractive and the quality of the images is goodto see. The audio aspect is 84.3%, meaning that the audio is audible by theaudience, and is comfortable to listen to. The content aspect, 88%, meaningthat the content of this video provides new knowledge about the studyprogram and the information can be understood properly. In the aspect oflanguage and writing, 85.3%, which means that the subtitles are appropriateand readable, articulation in conveying information is clear andunderstandable.